The Role of Fas-FasL Signaling Pathway in Induction of Apoptosis in Patients with Sulfur Mustard-Induced Chronic Bronchiolitis - Gila Pirzad; Mahvash Jafari; Sasan Tavana; Homayoon Sadrayee; Saeid Ghavami; Arezoo Shajiei; Mostafa Ghanei (Journal of Toxicology)
Sulfur mustard (SM) is an alkylating agent that induces apoptosis and necrosis in cells. Fas-Fas ligand (FasL) interaction could induce apoptosis as well. In this study, it was hypothesized that apoptosis might play an important role in the pathogenesis of SM-induced lung injury via Fas-FasL signaling pathway. In a case-control study, Fas and FasL levels, caspase-3 activity and percent of apoptotic cells were measured in bronchoalveolar lavage (BAL) fluid of patients 20 years after exposure to sulfur mustard and compared with the control group. Results show that Fas and FasL levels were significantly higher in BAL fluid cells in patients group compared with the control (P=.001). No significant differences were observed between mild and moderate-severe groups. BAL fluid cells caspase-3 activity was not significantly different among the mild, moderate-severe, and control groups. The data suggest that Fas-FasL-induced apoptosis was impaired in BAL fluid cells of SM-exposed patients which might be one of the initiators of pathogenesis in SM-induced lung injury in these patients.